KREATIVITAS GURU TAFSIR AMALY DALAM PENINGKATAN MOTIVASI BELAJAR SISWA DI SMA PRIMAGANDA JOMBANG - Nurul Indana; Umi Kalsum A (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2022)
Teacher creativity is the ability of teachers to express and realize the potential of their thinking power, so as to produce something new and can combine something that already exists into something better or interesting. Teachers are expected to have creativity in teaching which can increase students' learning motivation. This research is a field research ( field research ) which is qualitative, the form of research is descriptive qualitative using data collection techniques, namely observation, interviews, and documentation. Data analysis used descriptive qualitative analysis. The results of this study show: Student learning motivation at Primaganda High School: Student learning motivation at Primaganda High School increases much better when the teacher always provides innovation and encouragement to students.amalyinterpretation teacher in increasing student motivation at Primaganda High School is: by using methods, strategies and managing the class well, the teacher also uses humor and always gives praise and assessments to students so that student increases. While the supporting and inhibiting factors, namely the supporting factors include: students from Qur'anthe,and teachers at Primaganda High School have understood the material of Amal's interpretation. Factor  Inhibitors include:  factors that come from the students themselves such as lack of concern for students on the subject, external factors such as a less conducive learning atmosphere in the classroom, less references.